How Are Warm-Season Pastures’ Nutritive Value and Fermentation Characteristics Affected by Open Pasture, Silvopasture, and Sward Herbage Maturity? - Ferreira, Mariane Rodrigues [UNESP]; Cardoso, Abmael da Silva [UNESP]; Andrade, Marina Elizabeth Barbosa [UNESP]; Brito, Thais Ribeiro [UNESP]; Ruggieri, Ana Cláudia [UNESP] (MDPI, 2023)
This study aimed to evaluate the forage mass and nutritional value (NV) of Guinea Massai grass (Megathyrsus maximus × Megathyrsus infestum) in an open pasture (OP) or the silvopastoral system (SPS) at different stages of development (SDs). The experimental design was completely randomized, with five replications. The treatments were distributed in a factorial scheme 2 × 4, corresponding to types of systems (OP and SPS) and four SD (vegetative stage—S1, pre-flowering—S2, full flowering—S3 and maturity after flowering—S4). There was no interaction of the system × stage of plant development in any of the variables evaluated. The production of forage mass and Guinea Massai grass morphological components did not differ (p > 0.05) between SPS and OP. However, they differed between the SDs (p ≤ 0.05), with an increasing linear effect for forage mass, percentage of the stem, and dead material, and decreasing for leaf percentage and leaf: stem ratio. Only protein content differed (p < 0.05) among the chemical composition variables between culture systems. The shading caused by the SPS did not decrease the forage mass, NV, and in vitro dry matter digestibility of Guinea Massai grass compared to the system in OP. The advance of the SD of Guinea Massai grass increases the forage mass, with higher proportions of morphological components of low NV, such as stem and dead material. Silvopastoral system of Guinea Massai grass and eucalyptus is effective to prolongate the grazing season, with a greater amount of green leaves in the sward and better NV, without compromising herbage mass production in the forage growing season.
Keywords: forage management; Guinea Massai grass; integrated systems; nutritive value